Impact of exogenous hydrogen peroxide on osteogenic differentiation of broiler chicken compact bones derived mesenchymal stem cells - Tompkins, Y. H.; Liu, G.; Kim, W. K. (Frontiers in Physiology, 2023)
The effects of hydrogen peroxide (H2O2) on the osteogenic differentiation of primary chicken mesenchymal stem cells (MSCs) were investigated. MSCs were subjected to an osteogenic program and exposed to various concentrations of H2O2 for 14 days. Results showed that high concentrations of H2O2 (200 and 400 nM) significantly increased pro-apoptotic marker CASP8 expression and impaired osteogenic differentiation, as indicated by decreased mRNA expression levels of osteogenesis-related genes and reduced in vitro mineralization. In contrast, long-term H2O2 exposure promoted basal expression of adipogenic markers at the expense of osteogenesis in MSCs during osteogenic differentiation, and increased intracellular reactive oxygen species (ROS) production, as well as altered antioxidant enzyme gene expression. These findings suggest that long-term H2O2-induced ROS production impairs osteogenic differentiation in chicken MSCs under an osteogenic program.